Micromechanics of smart composite plates with periodically embedded actuators and rapidly varying thickness - Kalamkarov, Alexander L.; Challagulla, Krishna S.; Georgiades, Tasos (My University, 2006)
Asymptotic homogenization models for smart composite plates with periodically arranged embedded actuators and rapidly varying thickness are derived. The formulated models enable the determination of both local fields and effective elastic, actuation, thermal expansion, and hygroscopic expansion coefficients from three-dimensional local unit cell problems. The actuation coefficients, for example piezoelectric or magnetostrictive, characterize the intrinsic transducer nature of active smart materials that can be used to induce strains and stresses in a coordinated fashion. The theory is illustrated by means of examples pertaining to thin smart composite plates of uniform thickness, riband waferreinforced smart composite structures, and sandwich smart composite plates with honeycomb filler.
Keywords: Honeycombs; Ribs; Hygroscopicity; Magnetostrictive transducers